Evidence of binaural integration benefits following ARIA training for children and adolescents diagnosed with amblyaudia. (3rd August 2017) - Moncrieff, Deborah; Keith, William; Abramson, Maria; Swann, Alicia
Abstract: Objective : The purpose of this study was to demonstrate the efficacy of Auditory Rehabilitation for Interaural Asymmetry (ARIA) to improve dichotic listening scores in children and adolescents diagnosed with amblyaudia and other binaural integration deficits. Design : The study is a field experiment without randomisation. Study : Participants placed into groups based on dichotic listening test scores received four sessions of ARIA training. Baseline scores were compared to performance during the final session of training and to scores obtained 2 or more months after completion of ARIA. Sample : A total of 125 children participated at five different clinical sites. Results: Dichotic listening scores improved across all participants. Post hoc analyses demonstrated highly significant gains in non-dominant ear performance and reductions of interaural asymmetry among participants diagnosed with amblyaudia at both post-ARIA measurements. Participants in other diagnostic groups also showed significant benefits for some post-ARIA measures. Conclusions: Results demonstrate that ARIA training is an effective method for improving binaural integration skills among children and adolescents identified with dichotic listening weaknesses during assessments for auditory processing disorder (APD), especially for those diagnosed with amblyaudia. Benefits achieved following ARIA training remain stable across several months.